Effectiveness of Instructional Health Educational Vascular Access on Hemodialysis Patients' Knowledge at Al-Hussein Teaching Hospital in AL-Nasiriyah City. - naser, amer; mohammed, widad (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: The study aims: (1) To determine effectiveness of instructional health education vascular access on hemodialysis patients' knowledge, (2) To find out the association between effects of instructional health education vascular access and demographic characteristics of (age, gender and educational level). Methodology: A quasi experimental study –control study design is carried out at AL-Hussein Teaching Hospital in AL-Nasiriyah City, from 3November,2015 to 2 June, 2016. A non-probability (Purposive sample) of (80) patients with vascular access devices on maintenance hemodialysis patients divided into two group (40) patients as control study and (40) patients as study group , at AL- Hussein Teaching Hospital in Nasiriyah city. The data are collected through the use of semi-constructed questionnaire, which consists of three parts (1) sociodemographic data form (2) medical sheet information, and (3) main domains of health education, by direct interview technique with the patients. Reliability of the questionnaire is determined through a pilot study and the validity through a panel of experts. The data were described statistically and analyzed through use of the descriptive and inferential statistical analysis procedures. Results: The findings of the present study indicate that the effectiveness of health education vascular access on hemodialysis patient knowledge , since their relative sufficiency were under cutoff point, then followed by pre and posttest .There is a non-significant relationship between socio-demographic characteristics variable and reveal (no significant) correlation between gender with patients knowledge toward vascular access for both study and control group in pre and posttest except with age factor and level of education which revealed (no significant) in pretest for study group and pre and posttest for control group. While (significant) correlation between age factor and educational level and patient's knowledge toward vascular access in posttest of study group by P value < 0.05. Recommendations: The study recommended to provide educational program should be ongoing for patients with end stage renal disease initiated during the pre-hemodialysis stage and continued after maintenance hemodialysis with their caregivers to enhance their knowledge and skills about the vascular access , provide small booklist for caring.